Placental malaria among HIV-infected and uninfected women receiving anti-folates in a high transmission area of Uganda - Newman, Patrick M.; Wanzira, Humphrey; Tumwine, Gabriel; Arinaitwe, Emmanuel; Waldman, Sarah; Clark, Tamara D.; Cohan, Deborah (Malaria Journal, 2009)
HIV infection increases the risk of placental malaria, which is associated with poor maternal and infant outcomes. Recommendations in Uganda are for HIV-infected pregnant women to receive daily trimethoprim-sulphamethoxazole (TS) and HIV-uninfected women to receive intermittent sulphadoxine-pyrimethamine (SP). TS decreases the risk of malaria in HIV-infected adults and children but has not been evaluated among pregnant women.